Oligopoli Telekomunikasi dan Inovasi : Analisis Dampak Masuknya STARLINK bagi Industri Telekomunikasi di Indonesia - Muhammad Ridwan; Teuku Mohammad Daffa Al Islami; Putri Rahayu; Fatimah Rasyidah Az Zahra; Naerul Edwin Kiky Aprianto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This article explains the impact analysis of Starlink's entry into the telecommunications industry in Indonesia. In the modern era, the telecommunications industry in Indonesia has grown rapidly, but still faces geographical challenges and limited infrastructure. The telecommunications market in Indonesia is dominated by several large players, such as Telkomsel, XL Axiata, and Indosat, which control more than 95% of the market share. However, the presence of Starlink, a satellite internet network project owned by SpaceX, has changed the dynamics of this competition. Starlink offers high-speed internet connectivity without the need for fiber optic cable infrastructure, making it effective in reaching remote areas that are difficult to reach by traditional technology. By using thousands of small satellites in low orbit, Starlink offers a stable and reliable internet connection with low latency. This analysis uses a literature review method to compare and analyze theories related to oligopoly and technological innovation. The results show that Starlink has the potential to trigger innovation and improve the quality of service in the Indonesian telecommunications industry. Although initially expensive, Starlink is believed to become cheaper if demand increases, thus encouraging local providers to innovate and increase their service coverage.